2020
DOI: 10.3390/ijerph17228366
|View full text |Cite
|
Sign up to set email alerts
|

Brief Relaxation Practice Induces Significantly More Prefrontal Cortex Activation during Arithmetic Tasks Comparing to Viewing Greenery Images as Revealed by Functional Near-Infrared Spectroscopy (fNIRS)

Abstract: Background: There is little understanding on how brief relaxation practice and viewing greenery images would affect brain responses during cognitive tasks. In the present study, we examined the variation in brain activation of the prefrontal cortex during arithmetic tasks before and after viewing greenery images, brief relaxation practice, and control task using functional near-infrared spectroscopy (fNIRS). Method: This randomized controlled study examined the activation patterns of the prefrontal cortex (PFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…In addition, this study only focused on greenery and green model. Future research is thus suggested to explore more the biological aspects of greenery to see if there are other methods, such as brief relaxation practice, that are more effective to improve cognitive performance of employees [73]. Lastly, the current study mainly talked about psychological theories and did not study the biological aspects of greenery.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%
“…In addition, this study only focused on greenery and green model. Future research is thus suggested to explore more the biological aspects of greenery to see if there are other methods, such as brief relaxation practice, that are more effective to improve cognitive performance of employees [73]. Lastly, the current study mainly talked about psychological theories and did not study the biological aspects of greenery.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%
“…Starting from the neural bases that support IA, previous neuroscientific research has demonstrated activation of different portions of the right hemisphere, such as the supramarginal (SM) gyrus [10][11][12][13][14], the prefrontal cortex (PFC) [15], the dorsolateral prefrontal cortex (DLPFC) [16], and the frontopolar cortex [17] during the execution of interoceptive attention/awareness (IAA) tasks. While the right SM has been shown to be the "neural coder" of peripersonal space and corporeal awareness [10], the right DLPFC, instead, seems to orient and sustain attention by avoiding distractions in a goal-directed way [18].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, because of its sensitivity to movement artifacts, fMRI cannot be employed during real social interactions or movements, while functional Near-Infrared Spectroscopy (fNIRS) can be a useful technique that can overcome these limitations [46]. Indeed, the paucity of fMRI studies on IA tasks or brief relaxation practices could be due to the difficulty of an individual executing these practices in the fMRI scanner [17], and this proves even more difficult to perform during motor synchronization tasks. In contrast, fNIRS is particularly well-suited for evaluating the cortical responsivity in terms of hemodynamic variations related to information processing even in the presence of movement artifacts [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…The data in the first 10 s of each condition was used as a baseline for HbO, which was then subtracted from the HbO values of each task condition to obtain final HbO data. According to the previous studies (Zhang et al, 2020;Jang et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…The modified Beer Lambert Law (MBLL) was used to convert raw light intensities into concentration changes in oxygenated hemoglobin ( HbO2). The region of interest (ROI) was selected based on previous study (Zhang et al, 2020;Jang et al, 2021). The MNI coordinates for each channel were defined base on the equipment coordinates.…”
Section: Functional Near-infrared Spectroscopy Testmentioning
confidence: 99%